2019
DOI: 10.1186/s13000-019-0800-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SS18-SSX1/2 fusion transcripts in circulating tumor cells of patients with synovial sarcoma

Abstract: A recent study on 15 patients with synovial sarcoma demonstrated very low prevalence of tumor-specific fusion transcripts in peripheral blood specimens. Our results in an independent cohort of 38 patients with synovial sarcoma support these findings. Synovial sarcoma patients could greatly benefit from a non-invasive monitoring of tumor burden by liquid biopsies. However, given the low detection rate of SS18-SSX1/2 in circulation, we conclude that alternative markers other than the tumor-type specific fusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…These results confirm previously published data that quantification method by droplet digital PCR shows 10-fold greater sensitivity compared with RT-qPCR [57]. In agreement with the aforementioned report, a larger study by Przybyl et al incorporated 38 patients with synovial sarcoma and revealed that nested RT-PCR had a 5.3% sensitivity and 100% specificity in detection of SS18-SSX1/2 fusion transcript [28]. Another previously conducted study also by Przybyl et al had already shown that only 9% (3/34) of patients diagnosed with SS had measurable circulating tumor cells in their blood.…”
Section: Synovial Sarcoma (Ss)supporting
confidence: 92%
“…These results confirm previously published data that quantification method by droplet digital PCR shows 10-fold greater sensitivity compared with RT-qPCR [57]. In agreement with the aforementioned report, a larger study by Przybyl et al incorporated 38 patients with synovial sarcoma and revealed that nested RT-PCR had a 5.3% sensitivity and 100% specificity in detection of SS18-SSX1/2 fusion transcript [28]. Another previously conducted study also by Przybyl et al had already shown that only 9% (3/34) of patients diagnosed with SS had measurable circulating tumor cells in their blood.…”
Section: Synovial Sarcoma (Ss)supporting
confidence: 92%
“…Despite the absence of specific markers, various methods of cell isolation based on physical specificity (e.g., higher size and higher cell deformability of tumor cells) or biological properties (e.g., immunomagnetic isolation) have been proposed with success (Gabriel et al , 2016; Hayashi et al , 2017; Li et al , 2017). CTCs are detectable in bone sarcomas (Chinen et al , 2014; Benini et al , 2018) and STS patients (Braun et al , 2018; Mihály et al , 2018; Przybyl et al , 2019). To improve the sensitivity and specificity of detection and isolation of CTCs across sarcoma subtypes, investigators have been looking for universal sarcoma markers (Satelli et al , 2014; Li et al , 2018).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…SS18 was related to transcriptional misregulation in cancer and chromatin regulation (de Bruijn et al, 2006). This gene has been reported highly expressed in various kinds of malignant tumors (de Bruijn et al, 2006;Isfort et al, 2019;Przybyl et al, 2019). However, the roles of SS18 in breast cancer have not been investigated.…”
Section: Discussionmentioning
confidence: 99%